Abiotic and biotic regulation on carbon mineralization and stabilization in paddy soils along iron oxide gradients. (September 2021) - Jeewani, Peduruhewa H.; Van Zwieten, Lukas; Zhu, Zhenke; Ge, Tida; Guggenberger, Georg; Luo, Yu; Xu, Jianming
Abstract: Iron (Fe) oxides regulate soil organic carbon (C) content via balancing C processes of stabilization and mineralization. However, abiotic and biotic mechanisms are involved in stabilization (e.g., by adsorption and/or co-precipitation) and decomposition (e.g., by shifting the microbial community) of paddy soil rich in iron oxides remains poorly understood. We examined the mineralization and stabilization of maize-straw-derived C (δ 13 C = 5000‰), soil priming effects (PE), and soil microbial community structure in four paddy soils, along with Fe oxide concentrations gradient ranging from 13.7 to 55.8 g kg −1 soil (Fe-13, Fe-25, Fe-42, and Fe-55). The paddy soil with the highest Fe content (Fe-55) stabilized 20.5 mg 13 C kg −1 soil of the maize-straw-derived C, being significantly greater ( P < 0.05) than Fe-13 (5 mg 13 C kg −1 soil). The high C:Fe molar ratio of Fe-55 suggests the main pathway of stabilizing the maize-straw-derived C via co-precipitation as Fe-OM. Larger stabilization in Fe-55 led to less CO2 emission from maize and SOM, e.g., Fe-55 had 12–16% lower straw mineralization and 8–11% lower PE than Fe-13 during the first 7 days of incubation. Random forest analysis further revealed that Proteobacteria and Actinobacteria (the keystone species, i.e., Gaiella ) gave the largest contribution to maize-straw mineralization and PE, while microbial diversity and some microorganisms featured with filamentous hyphae contributed to C stabilization. This study confirmed that the concentration of Fe oxide in paddy soils plays a central role in C sequestration via biotic and abiotic processes, including i) modulation of microbial community diversity and composition, especially the abundance of fungi and Actinobacteria, and ii) physicochemical stabilization of maize-straw-derived C through the formation of Fe-OM complexes via co-precipitation. Highlights: Iron (Fe) oxide rich-soil had lower maize-straw mineralization and SOM priming. Co-precipitation was the main physicochemical stabilization mechanism of C. The highest microbial diversity was found in Fe rich-soil. Fe rich-soils governs C stabilization via Fe-OM complexation and limiting C availability to microbes.